The Perfect Marriage: Perfect #1 - Rose, Jeneva; Riedlinger, Sarah (Ashland, Oregon : Blackstone Publishing, 2024)
Sarah Morgan is a successful and powerful defense attorney in Washington D.C. Her husband Adam is a struggling writer who has had little success in his career. He begins to tire of his and Sarah's relationship as she is constantly working. Out in the secluded woods, at Adam and Sarah's second home, Adam engages in a passionate affair with Kelly Summers. Then, one morning everything changes. Adam is arrested for Kelly's murder. She had been found stabbed to death in Adam and Sarah's second home. Sarah soon finds herself playing the defender for her own husband, a man accused of murdering his mistress.
new book 2025 summer.
Keywords: Women lawyers -- Fiction; Criminal defense lawyers -- Fiction; Murder -- Investigation -- Fiction; Mistresses -- Fiction -- Crimes against; Adultery -- Fiction; Marital conflict -- Fiction; Morgan, Sarah; Washington (D.C.) -- Fiction; Suspense fiction; Psychological fiction; Thriller fiction; Legal fiction